Synthesis of amide and sulfonamide substituted N-aryl 6-aminoquinoxalines as PFKFB3 inhibitors with improved physicochemical properties. Issue 4 (15th February 2019) - Boutard, Nicolas; Białas, Arkadiusz; Sabiniarz, Aleksandra; Guzik, Paweł; Banaszak, Katarzyna; Biela, Artur; Bień, Marcin; Buda, Anna; Bugaj, Barbara; Cieluch, Ewelina; Cierpich, Anna; Dudek, Łukasz; et al.
Graphical abstract: Abstract: In oncology, the "Warburg effect" describes the elevated production of energy by glycolysis in cancer cells. The ubiquitous and hypoxia-induced 6-phosphofructo-2-kinase/fructose-2, 6-biphosphatase 3 (PFKFB3) plays a noteworthy role in the regulation of glycolysis by producing fructose-2, 6-biphosphate (F-2, 6-BP), a potent activator of the glycolysis rate-limiting phosphofructokinase PFK-1. Series of amides and sulfonamides derivatives based on a N -aryl 6-aminoquinoxaline scaffold were synthesized and tested for their inhibition of PFKFB3 in vitro in a biochemical assay as well as in HCT116 cells. The carboxamide series displayed satisfactory kinetic solubility and metabolic stability, and within this class, potent lead compounds with low nanomolar activity have been identified with a suitable profile for further in vivo evaluation.